Photoelectron momentum distribution of hydrogen atoms in a superintense ultrashort high-frequency pulse - Wang, Jun; Li, Gen-Liang; Liu, Xiaoyu; Zhu, Feng-Zheng; Jiao, Li-Guang; Liu, Aihua (Frontiers in Physics, 2022)
We use a numerically solved time-dependent Schrödinger equation for calculating the photoelectron momentum distribution of ground-state hydrogen atoms in the presence of superintense ultrashort high-frequency pulses. It is demonstrated that the dynamic interference effect within a superintense XUV laser beam has the ability to significantly alter the photoelectron momentum distribution. In our work, a clearly visible dynamic interference pattern is observed when hydrogen atoms are exposed to a superintense circularly polarized laser pulse with a photon energy of ℏω = 53.605 eV, which has previously been found for linearly polarized pulses or the weakly bounded model H− system for circularly polarized pulses. Angular-distorted interference arises for linear superintense XUV pulses of similar intensity. The significant differences in photoelectron momentum distributions that have been seen by linearly and circularly polarized XUV pulses are caused by the Coulomb rescattering phenomenon.